2008
DOI: 10.1080/18811248.2008.9711882
|View full text |Cite
|
Sign up to set email alerts
|

Batch Crystallization of Uranyl Nitrate

Abstract: Batch crystallization of uranyl nitrate is carried out in order to obtain fundamental data required for the development of reprocessing involving crystallization. Particular attention is paid to the development of a method for predicting the concentrations of uranium and nitric acid in the mother liquor and the amount of uranyl nitrate crystals produced. Initial concentrations of uranyl nitrate and nitric acid are 500-600 g/l and 4-6 mol/l, respectively, corresponding to the condition of a dissolver solution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Validation of the numerical method for crystallization has been performed by comparison with experimental results of the batch crystallization. 10) Although the amount of the initial supply of the solution is used instead of the volumetric flow rate, the calculated results are in close agreement with the experimental ones and the error is within 5%.…”
Section: Calculation Of Crystallizationsupporting
confidence: 71%
See 1 more Smart Citation
“…Validation of the numerical method for crystallization has been performed by comparison with experimental results of the batch crystallization. 10) Although the amount of the initial supply of the solution is used instead of the volumetric flow rate, the calculated results are in close agreement with the experimental ones and the error is within 5%.…”
Section: Calculation Of Crystallizationsupporting
confidence: 71%
“…At the minimum point, the solution still has a certain amount of U and the recovery of the entire amount of U is not achievable by a single stage of crystallization. A recent experimental study 10) has shown that the recovery of U is at most about 95% when the solution, which contains 400-600 g-U/l, is cooled to À10 C. This low separation efficiency can cause losses of U and Pu into highly active waste (HAW). The system, therefore, requires recycling of the mother liquor from the U-Pu co-crystallization to avoid the losses.…”
Section: Introductionmentioning
confidence: 99%
“…Uranyl nitrate hexahydrate (UNH), from laboratory stock was purified after treatment [17] of 100 g batches in 10 M HNO 3 at 70 °C and cooled to − 10 °C in a freezer for 12 h. HNO 3 (ACS reagent, 68-70%) was purchased from Sigma Aldrich. Deionized water (18.2 MΩ•cm) was used for the dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of the U VI photocatalytic reduction by O 2 could be attributedt ot he fast oxidation of U V and/or U IV . [20][21][22] Several TiO 2 photocatalytic studies have been undertaken for the As and Us ystems, and most of them have been recently reviewed, [23][24][25][26] including contributionsf rom our group. [14][15][16] For this reason, the World Health Organization( WHO)r ecommends no more than 10 mgL À1 of arsenic in drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…[16,18,19] Uranyl nitrate in nitric acid is formed in the PUREX process,t he major chemicalt echnique used to recover uranium from spent nuclear fuel; [20] the separation of U VI from this aqueous solutioni s an active research field. [20][21][22] Several TiO 2 photocatalytic studies have been undertaken for the As and Us ystems, and most of them have been recently reviewed, [23][24][25][26] including contributionsf rom our group. [27][28][29][30] Therefore, stopped-flow studies on As III /As V and uranyl nitrate in TiO 2 photocatalytic systems seemed to be very appealing.…”
Section: Introductionmentioning
confidence: 99%